CHANGES IN PHYSICAL QUALITY OF OXISOLS UNDER DIFFERENT MANAGEMENT SYSTEMS IN THE BRAZILIAN CERRADO - Feitosa, Carlos E. L.; Costa, Pedro H. dos S.; Meneses, Kamila C. de [UNESP]; Oliveira, Ulisses C. de; Farias, Maryzelia F. de (Soc Brasil Engenharia Agricola, 2020)
Soil compaction in agricultural areas has greatly increased in recent decades due to intensive farming practices, including short-cycle crops and machinery intensification. This study aimed to evaluate the impacts of management systems on the physical quality of a dystrophic Yellow Oxisol, in the Cerrado region of Brazil. Treatments consisted of five soil management systems, with five replications (native forest [control], slash-and-burn agriculture, pasture, no-tillage, and conventional tillage). Data analysis was performed using a completely randomized experimental design. All systems were analyzed for soil density, macroporosity, microporosity, total porosity, hydraulic conductivity, infiltration, water retention curve, penetration resistance, and soil quality index (S index). The systems had significant effects on soil structure, and the evaluated properties responded well to changes promoted by them. No-tillage implementation raised soil resistance in the area previously damaged by intensive farming. Moreover, soils under pasture and slash-and-burn systems presented higher water retention in field capacity and higher S indexes, thus having a better structural quality.
Keywords: S index; land cover change; physical properties; infiltration; soil compaction